Acute Pancreatitis and Use of Pancreatitis-Associated Drugs: A 10-Year Population-Based Cohort Study. Issue 7 (October 2015) - Bertilsson, Sara; Kalaitzakis, Evangelos
Abstract : Objectives: To assess the use of acute pancreatitis (AP)–associated drugs in patients with AP, the relation between sales of these drugs and the incidence of AP, and the potential impact on AP severity and recurrence. Methods: All patients with incident AP between 2003 and 2012, in a well-defined area, were retrospectively identified. Data regarding AP etiology, severity, and recurrence and use of AP-associated drugs were extracted from medical records. Drugs were classified according to an evidence-based classification system. Annual drug sales data were obtained from the Swedish drug administration service. Results: Overall, 1457 cases of incident AP were identified. Acute pancreatitis–associated drug users increased from 32% in 2003 to 51% in 2012, reflecting increasing user rates in the general population. The incidence of AP increased during the study period but was not related to AP-associated drug user rates ( P > 0.05). Recurrent AP occurred in 23% but was unrelated to AP-associated drug use ( P > 0.05). In logistic regression analysis, after adjustment for comorbidity, AP-associated drug use was not related to AP severity ( P > 0.05). Conclusions: Use of AP-associated drugs is increasingly frequent in patients with AP. However, it does not have any major impact on the observed epidemiological changes in occurrence, severity, or recurrence of AP. Abstract : Supplemental digital content is available in the text.